Influenza A Virus Hemagglutinin and Other Pathogen Glycoprotein Interactions with NK Cell Natural Cytotoxicity Receptors NKp46, NKp44, and NKp30 - Jasmina M. Luczo; Sydney L. Ronzulli; Stephen M. Tompkins (Viruses, 2021)
Natural killer (NK) cells are part of the innate immunity repertoire, and function in the recognition and destruction of tumorigenic and pathogen-infected cells. Engagement of NK cell activating receptors can lead to functional activation of NK cells, resulting in lysis of target cells. NK cell activating receptors specific for non-major histocompatibility complex ligands are NKp46, NKp44, NKp30, NKG2D, and CD16 (also known as FcγRIII). The natural cytotoxicity receptors (NCRs), NKp46, NKp44, and NKp30, have been implicated in functional activation of NK cells following influenza virus infection via binding with influenza virus hemagglutinin (HA). In this review we describe NK cell and influenza A virus biology, and the interactions of influenza A virus HA and other pathogen lectins with NK cell natural cytotoxicity receptors (NCRs). We review concepts which intersect viral immunology, traditional virology and glycobiology to provide insights into the interactions between influenza virus HA and the NCRs. Furthermore, we provide expert opinion on future directions that would provide insights into currently unanswered questions.